(untitled) (Biological Sciences - PJSIR, 2023)
The present study was conducted for quantitative and qualitative analysis of bioaerosols in both tannery environment and control group. A total of eight air samples was collected from four wet-blue leather tanneries and the control group during September-December, 2019. Portable volumetric dust sampler was used to sample bioaerosols. Temperature, humidity and gases were monitored by portable aeroqual series 500. The respiratory micro-biota was identified through 16S rRNA gene sequencing. The bacterial count in tannery air was estimated to be 510 to 750 C.F.U/m3, whereas the number of fungi was 600 to 900 C.F.U/m3. The bacterial spectrum measured in the control community, on the other hand, was 400 to 492 C.F.U/m3. However, no fungal strains was found in the control group’s samples. Among four wet-blue leather tanneries, Staphylococcus aureus, S. hominis, S. gallinarum, Klebsiella varricola were the bacterial, while Aspergillus versicolor, A. flavus, Candida parapsilosis and Penicillium chrysogenum were the fungal species identified at the molecular level. However, in control group S. hominis, S. warneri, epidermidis, Micrococcus luteus (M) and Bacillus subtilis (B.) were identified without any fungal species